THE PARENTS COMMUNICATION PATTERNS OF PREMARITAL SEXUAL BEHAVIOR IN VOCATIONAL SCHOOL “X” - Yuyun Triwahyuni; Dewi Rokhmah; Ristya Widi Endah Yani (Aloha International Journal of Health Advancement (AIJHA), 2019)
Premarital sexual behavior is one of the problems in adolescents. One of the factors causing premarital sexual behavior in adolescents is the role of parental communication patterns. This research was conducted at the Vocational School in September 2019. Researchers wanted to find out the influence of parental communication patterns on premarital sexual behavior in adolescents. The results showed that most students had good communication patterns with their parents by 47.2%, while as many as 56.5 % of students have good premarital behavior. Keywords * communication patterns, * premarital sexual behavior